Method for extracting furosin from chongyang wood leaves - WANG LIN; WANG FENG; ZHANG FACHENG (2012)
The invention relates to a method for extracting furosin from chongyang wood leaves, which is easy and simple to operate, less in pollution and small in energy consumption and includes the following steps: getting the chongyang wood leaves, smashing, adding the smashed chongyang wood leaves in a CO2 supercritical extractor, obtaining extract, absorbing the extract through strongly-alkaline styrene type anion exchange resin, eluting through 0.5mol/L of NaOH solution, collecting, eluting, filtering, passing though the strongly-alkaline styrene type anion exchange resin, colleting effluent liquid, filtering, concentrating, drying, adding the effluent liquid on a silica gel chromatographic column, eluting by methanol-chloroform mixed solvent with 5:1 volume ratio, collecting eluant, concentrating, adding acetone crystal, separating crystal, washing, drying and obtaining the furosin. The method for preparing the furosin is high in product purity, easy to achieve and high in industrialization.